Rapid identification of Staphylococcus aureus and the mecA gene from BacT/ALERT blood culture bottles by using the LightCycler system - Shrestha, Nabin K; Tuohy, Marion J; Hall, Gerri S; Isada, Carlos M; Procop, Gary W (Journal of clinical microbiology, 2002)
One hundred BacT/ALERT blood culture bottles growing gram-positive cocci in clusters were cultured and studied by LightCycler PCR for the sa442 and mecA genes. PCR was 100% sensitive and specific for detecting Staphylococcus aureus and methicillin resistance in S. aureus but was less accurate for methicillin resistance in coagulase-negative staphylococci.